A hybrid fermatean fuzzy framework for evaluating climate-responsive supply network strategies - Ayyildiz, Ertugrul; Yildirim, Betul; Aydin, Nezir (SPRINGER, 2026)
Despite the growing importance of climate change adaptation, current studies offer limited methodologies for selecting optimal supply network strategies under uncertain and dynamic environmental conditions. This study aims to fill this gap by identifying and prioritizing the most suitable supply network strategies considering sustainability and climate change impacts. A novel hybrid multi-criteria decision-making (MCDM) approach is developed, integrating Fermatean Fuzzy Analytical Hierarchy Process (FF-AHP) and Fermatean Fuzzy Weighted Integrated Sum Product (FF-WISP) methods to address uncertainty and complexity in the decision-making process. First, a comprehensive hierarchical evaluation framework, consisting of three levels of criteria, including environmental, resilience, and socioeconomic dimensions, was developed through literature review and expert input. FF-AHP was applied to calculate the relative importance of these criteria, while FF-WISP ranked four strategic alternatives. The results highlight Hybrid (Global + Local) with Flexible Logistics as the most effective strategy, followed by Regional Sourcing with High-Resilience Investment. Sensitivity analysis with randomized expert weights confirmed the robustness of the proposed model. This study contributes a flexible and practical decision-support tool for policymakers and supply chain managers facing climate uncertainty. Future research may extend this model by integrating smart logistics technologies and renewable energy-based criteria for broader sustainability applications.
Keywords: Supply networks; Multi-criteria optimization; Fermatean fuzzy sets; Sustainability; Climate change; CHAIN; Operations Research & Management Science